A novel scheme for unified streamlined traffic management in 5G backhaul network - Thippanna, Deepa; Jayappa, Praveen (Institute of Advanced Engineering and Science, 2024)
The issues associated with the 5G backhaul network act as the underlying reason for concern. Existing literature towards the 5G backhaul network offers various ranges of sophisticated schemes that are yet to possess open-end issues. Therefore, the proposed study introduces a novel scheme for effective 5G backhaul network traffic management. The scheme hypothesizes that if an efficient gateway node is selected, it can better communicate between the macro-base station and the core network. The study contributes to developing a sophisticated system design to identify the blockage region, a macro-base station, and a small base station. These attributes incorporate the capability of a gateway node to identify the bottleneck condition during peak traffic situations in the 5G backhaul network. The study outcome shows better communication performance in contrast to the existing system. The study outcome shows the proposed scheme to offer 47% increased throughput, 80% reduced latency, and 55% reduced algorithmic processing time in contrast to existing schemes.